Surgical site infections in clean and clean contaminated surgeries in a tertiary care teaching hospital - Tolpadi, Anuradha G.; Mane, Abhijeet K.; Dhayagude, Snehal V.; Modak, Meera S.; Dongare, Dhananjay M.; Tendulkar, Akshata S.; Mahadik, Prerana U.; Lamkhade, Pallavi (International Surgery Journal, 2021)
Background: Despite major advances in infection control interventions, health care-associated infections (HAI) remain a major public health problem and patient safety threat worldwide. Surgical site infections (SSI) are among the most commonly reported Hospital acquired infections (HAI). Methods: This was a prospective observational study conducted in a tertiary care hospital over a period of one year from May 2019 to April 2020. Total 2382 patients who underwent clean and clean contaminated surgeries were included in the study. The data on demographics, type of surgery, duration of surgery, day of SSI event, use of prosthesis, comorbidities, post-operative stay and resuturing was collected and analyzed. From suspected patients of SSI, pus aspirate/swab was sent for culture and susceptibility. Results: Total 2382 clean and clean contaminated surgeries were included in the study. The incidence of SSI was 2.05%. Association between SSI and gender, age group and whether the surgeries were planned or were emergency surgeries was noted. In 37 (75.51%) patients who developed SSI the post-operative stay was prolonged (>7days). 3 (6.1%) patients had to undergo resuturing due to gaping in the surgical wound. 18(36.73%) cases of SSI were diagnosed after discharge from hospital. The predominant organism causing SSI was Escherichia coli followed by Staphylococcus aureus and Coagulase negative Staphylococcus (CONS). Conclusions: Regular surveillance of SSI with feedback of appropriate data to the stakeholders is desirable to reduce SSI rate. Post patient discharge, surveillance of SSI is challenging but it needs to be addressed by infection control team to identify cases of SSI accurately.